2018
DOI: 10.5604/01.3001.0012.0925
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Quantification of Free and Forced Convection via the Decoupling of Thermo-Mechanical and Thermo-Fluidic Simulations of Machine Tools

Abstract: Thermo-elastic deformations represent one of the main reasons for positioning errors in machine tools. Investigations of the thermo-mechanical behaviour of machine tools, especially during the design phase, rely mainly on thermo-elastic simulations. These require the knowledge of heat sources and sinks and assumptions on the heat dissipation via convection, conduction and radiation. Forced convection such as that caused by moving assemblies has both a large influence on the heat dissipation to the surrounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This can be achieved by introducing a clustering algorithm (CA) and characteristic diagrams (CDs) in the workflow. _____________ 1 Fraunhofer Institute for Machine Tools and Forming Technology IWU, Chemnitz, Germany 2 Dresden University of Technology, Institute of Scientific Computing, Dresden, Germany CDs are continuous maps of a set of input variables onto a single output variable and consists of multidimensional grids, refer to the work by Priber [2] and Naumann et al [3]. Using a limited number of CFD simulations, the environmental influences (parameters) on a machine surface can be mapped on to its corresponding heat transfer coefficient (HTC) values at certain optimal node points.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be achieved by introducing a clustering algorithm (CA) and characteristic diagrams (CDs) in the workflow. _____________ 1 Fraunhofer Institute for Machine Tools and Forming Technology IWU, Chemnitz, Germany 2 Dresden University of Technology, Institute of Scientific Computing, Dresden, Germany CDs are continuous maps of a set of input variables onto a single output variable and consists of multidimensional grids, refer to the work by Priber [2] and Naumann et al [3]. Using a limited number of CFD simulations, the environmental influences (parameters) on a machine surface can be mapped on to its corresponding heat transfer coefficient (HTC) values at certain optimal node points.…”
Section: Introductionmentioning
confidence: 99%
“…A single CFD simulation could take around one hour to complete. The realistic discretization or proper training of CDs would involve 158 CFD Simulations, (Glänzel et al [1]). Thus, approximately six days would be required to perform CFD simulations on a normal computational system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires the adaptation of the heat transfer coefficients (HTCs), which are boundary conditions of the FE models. Naumann et al have shown how these HTCs can be obtained through fluid (CFD) simulations for natural and varying forced convection scenarios [12].…”
mentioning
confidence: 99%
“…machine learning and regression methods -Data driven methods generally require vast amounts of training data for modelling and are hardly transferable[21][22][23][24][25][26][27][28] thermomechanical behavior (incl. airflows → CFD & ambient temperatures), thus requires high computationnal power & detailed modelling[29][30][31][32][33]…”
mentioning
confidence: 99%